2000
DOI: 10.1093/hmg/9.16.2395
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methyltransferases of mammals

Abstract: The biological significance of 5-methylcytosine was in doubt for many years, but is no longer. Through targeted mutagenesis in mice it has been learnt that every protein shown by biochemical tests to be involved in the establishment, maintenance or interpretation of genomic methylation patterns is encoded by an essential gene. A human genetic disorder (ICF syndrome) has recently been shown to be caused by mutations in the DNA methyltransferase 3B (DNMT3B) gene. A second human disorder (Rett syndrome) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
1,282
3
46

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,814 publications
(1,339 citation statements)
references
References 52 publications
8
1,282
3
46
Order By: Relevance
“…Methylation of CpG sites in the promoter region of a gene is commonly associated with repression of gene expression 10, 11, 12. DNA methylation occurs through the activity of DNA methyltransferases (DNMTs), particularly DNMT1 postdevelopment 13, 14, 15. Recently, DNA methylation has been shown to differentially regulate flow‐mediated endothelial gene expression through DNMT1,16, 17, 18, 19 although the role of DNA methylation in the regulation of arteriogenesis has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of CpG sites in the promoter region of a gene is commonly associated with repression of gene expression 10, 11, 12. DNA methylation occurs through the activity of DNA methyltransferases (DNMTs), particularly DNMT1 postdevelopment 13, 14, 15. Recently, DNA methylation has been shown to differentially regulate flow‐mediated endothelial gene expression through DNMT1,16, 17, 18, 19 although the role of DNA methylation in the regulation of arteriogenesis has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Three DNA methyltransferase (DNMT) enzymes have been identified in eukaryotic cells (Bestor, 2000;Rountree et al, 2001). DNMT1 is generally considered to be a maintenance methylase, although it also has de novo methylase activity (Bestor, 2000;Robertson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1 is generally considered to be a maintenance methylase, although it also has de novo methylase activity (Bestor, 2000;Robertson, 2002). Both DNMT3A and DNMT3B catalyse de novo methylation of DNA sequences (Li, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reported that the effect of methylation-inducing gene silence may be greatly different from antisense oligonucleotide. [18][19][20] Theoretically, the epigenetic mark (DNA methylation) imposed is very stable in the genome and heritable through cell divisions. In our studies, we found that down-regulatory effects of SurKex1 on survivin expression persisted only up to passage 3 but weakened drastically in passage 4 after termination of SurKex1 transfection (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17] DNA methylation is a critical epigenetic modification that silences gene transcription. [18][19] Yao et al 20 have devised a method to inhibit transcriptional initiation by constructing short methylated oligonucleotides which induce DNA methylation at specific loci. In this study, we used SurKex1, a methylated sense oligonucleotide designed emulating the method of Yao et al 20 , as an alternative strategy to target survivin and investigated its efficacy for the suppression of survivin expression and the consequent apoptotic induction potential in NCI-H460 cells.…”
Section: Introductionmentioning
confidence: 99%